2021
DOI: 10.1111/ecog.05229
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scaling of food web structure across European biogeographical regions

Abstract: The species-area relationship (SAR) is one of the most well-established scaling patterns in ecology. Its implications for understanding how communities change across spatial gradients are numerous, including the effects of habitat loss on biodiversity. However, ecological communities are not mere collections of species. They are the result of interactions between these species forming complex networks that tie them together. Should we aim to grasp the spatial scaling of biodiversity as a whole, it is fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 60 publications
3
29
1
Order By: Relevance
“…Recent theoretical and empirical work has revealed potential mechanisms driving changes in food web structure across spatial scales 4–6 . Among those, SARs have been identified as an important driver of NARs 5,6 . In accordance with these studies, we found that SARs were the main factor that drives NARs of soil bacteria and fungi (Figures 2, S1, S3, and S4).…”
Section: Figuresupporting
confidence: 85%
“…Recent theoretical and empirical work has revealed potential mechanisms driving changes in food web structure across spatial scales 4–6 . Among those, SARs have been identified as an important driver of NARs 5,6 . In accordance with these studies, we found that SARs were the main factor that drives NARs of soil bacteria and fungi (Figures 2, S1, S3, and S4).…”
Section: Figuresupporting
confidence: 85%
“…We suggest using high‐resolution assessments over large spatial scales to improve our understanding of ecosystem structure and function. By comparing the properties of ecological networks at different spatial resolutions (50, 10 and 1 km 2 ), it is possible enhance fundamental knowledge (Galiana et al, 2021), but also determine the necessary scales for robust decision‐making based on ecological network data.…”
Section: Developing a Mechanistic Understanding Of Ecological Patternsmentioning
confidence: 99%
“…"; the most promising solutions involve examining the spatial consistency of network area relationships (Fortin et al, 2021; see e.g. Galiana et al, 2018Galiana et al, , 2019Galiana et al, , 2021, which is impossible in the absence of enough information about the network itself. This suggests that inferred metawebs should be further downscaled to allow for a posteriori analyses.…”
Section: The Metaweb Embeds Ecological Hypotheses and Practicesmentioning
confidence: 99%